Mismatch Responses Evoked by Sound Pattern Violation in the Songbird Forebrain Suggest Common Auditory Processing With Human - Mori, Chihiro; Okanoya, Kazuo (Frontiers in Physiology, 2022)
Learning sound patterns in the natural auditory scene and detecting deviant patterns are adaptive behaviors that aid animals in predicting future events and behaving accordingly. Mismatch negativity (MMN) is a component of the event related potential (ERP) that is reported in humans when they are exposed to unexpected or rare stimuli. MMN has been studied in several non-human animals using an oddball paradigm by presenting deviant pure tones that were interspersed within a sequence of standard pure tones and comparing the neural responses. While accumulating evidence suggests the homology of non-human animal MMN-like responses (MMR) and human MMN, it is still not clear whether the function and neural mechanisms of MMR and MMN are comparable. The Java sparrow is a songbird that is vocal learner and highly social, and maintains communication with flock members using frequently repeated contact calls and song. We expect that the songbird is a potentially useful animal model that will broaden our understanding of the characterization of MMR. Because of this, we chose this species to explore MMR to the deviant sounds in oddball paradigm using both pure tones and natural vocalizations. MMRs were measured in the caudomedial nidopallium (NCM), a higher order auditory area. Significant differences were observed in the negative component between deviant and standard ERPs both to pure tones and natural vocalizations in the oddball sequence. However, the subsequent experiments using the randomized standards and regular pattern sequence suggest the possibility that MMR elicited in the oddball paradigm reflects the adaptation to a repeated standard sound, but not the genuine deviance detection. Further, we presented contact call triplet sequences and investigated MMR in the NCM in response to sound sequence order. We found a significant negative shift in response to a difference in sequence pattern. This demonstrates MMR elicited by violation of the pattern of triplet sequence and the ability to extract sound sequence information in the songbird auditory forebrain. Our study sheds light to the electrophysiological properties of auditory memory processing, expanding the scope of characterization of MMR beyond simple deviance detection, and provide a comparative perspective on syntax processing in humans.